Cambridge CAE - Practice Tests / For the Certificate in Advanced English Examination - Fowler W.S (New Editions, 2000)
This book has been designed to familiarize students with the exact format of each part of the Cambridge Certificate in Advanced English examination as well as to expand their vocabulary and improve the skills required in the examination. Introduction, Tests One to Six, Photographs for Speaking Papers, Appendices, Verbs Taking Prepositions, Verb - Noun - Adjective - Phrase Relationships.